Model‐Informed Drug Development for Ixazomib, an Oral Proteasome Inhibitor. Issue 2 (23rd March 2018) - Gupta, Neeraj; Hanley, Michael J.; Diderichsen, Paul M.; Yang, Huyuan; Ke, Alice; Teng, Zhaoyang; Labotka, Richard; Berg, Deborah; Patel, Chirag; Liu, Guohui; van de Velde, Helgi; Venkatakrishnan, Karthik
Abstract : Model‐informed drug development (MIDD) was central to the development of the oral proteasome inhibitor ixazomib, facilitating internal decisions (switch from body surface area (BSA)‐based to fixed dosing, inclusive phase III trials, portfolio prioritization of ixazomib‐based combinations, phase III dose for maintenance treatment), regulatory review (model‐informed QT analysis, benefit–risk of 4 mg dose), and product labeling (absolute bioavailability and intrinsic/extrinsic factors). This review discusses the impact of MIDD in enabling patient‐centric therapeutic optimization during the development of ixazomib.